Odpowiedzi

2010-03-27T17:00:44+01:00
A)(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-6-5x=-11-2x
-5x= -5-2x
-3x=-5
x=-1,(6)

b) (4-x)-(2x+3)+(x-4)=-(2x-3)-(x-7)
4-x-2x-3+x-4=-2x+3-x+7
-3-2x=-3x+10
-2x=-3x+13
x= 13

c)(4x-5)+(x-7)-(2x-8)=(-3x)+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
3x-4=2x+10
3x= 2x+14
x=14

d)-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
-8=8x-13
5=8x
0,625=x
2010-03-27T17:10:00+01:00
A) (3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
5x-2x-2x-3x-x=5+4-3-4-7
-3x=-5
x=5/3
b) (4-x)-(2x+3)+(x-4)=-(2x-3)(x+7)
4-x-2x-3+x-4=-(2x^2+14x-3x-21)
4-x-2x-3+x-4=-2x^2+14x-3x-21
2x^2+14x-3x-2x=21+3-4
2x^2+9x=20
x^2+4,5x=10
c) (4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
7x=14
x=2
d)-(4-2x)-(2x+4)=2(2x-1)-(4-x)
-4+2x-2x-4=4x-2-4+x
-3x=2
x=-2/3
2010-03-27T17:16:36+01:00
A) 3-2x-x-4-2x-5=3x-4-5x-7
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-4-7+5+4-3
-3x=-5 /:(-3)
x=5/3

b) 4-x-2x-3+x-4=2x²+14x-3x-21
-2x²-14x+3x-x-2x+x+4-4+21=0
-2x²-13x+21=0

c) 4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x=4+6-8+7+5
7x=14
x=2

d) -4+2x-2x-4=4x-2-4+x
-4=4x-2+x
-4x-x=2+4
-5x=-2 /:(-5)
x=2/5